Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(5\times6\right)^2\) = 302 = 900 (1)
\(5^2\times6^2\) = 25 . 36 = 900 (2)
Từ (1) và (2) ⇒ (5 . 6 )2 = 52 . 62 ( = 900)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài làm :
\(\frac{4^6\times9^5+120\times6^9}{8^4\times3^{12}-6^{11}}\)
\(=\frac{\left(2^2\right)^6\times\left(3^2\right)^5+2^3\times5\times3\times\left(2\times3\right)^9}{\left(2^3\right)^4\times3^{12}-\left(2\times3\right)^{11}}\)
\(=\frac{2^{12}\times3^{10}+2^3\times5\times3\times2^9\times3^9}{2^{12}\times3^{12}-2^{11}\times3^{11}}\)
\(=\frac{2^{12}\times3^{10}\times\left(1+5\right)}{2^{11}\times3^{11}\times\left(2\times3-1\right)}\)
\(=\frac{2\times6}{3\times5}\)
\(=\frac{4}{5}\)
Học tốt nhé
![](https://rs.olm.vn/images/avt/0.png?1311)
63+3x62+33/13
=63+31x62+33/13
=62x31x(6+32)/13
=1620/13
Em nghĩ là thế !
![](https://rs.olm.vn/images/avt/0.png?1311)
= (2.3)^3+ 3. ( 2.3)^2 + 3^3 / -13
= 2^3 .3^3 + 3. 3^2 . 2^2 + 3^3 / -13
= 3^3. ( 2^3 + 2^2 + 1) /-13
= 27.13/-13
= -27
\(\frac{6^3+3\cdot6^2+3^3}{-13}=\frac{6^2\left(6+3\right)+3^2\cdot3}{-13}=\frac{36\cdot9+9\cdot3}{-13}=\frac{39\cdot9}{-13}=-3\cdot9=-27\)
11.6x - 1 + 2.6x + 1 = 11.611 + 2.613
<=> 6x - 1(11 + 2.62) = 611(11 + 2.62)
<=> 6x - 1 = 611
<=> x - 1 = 11
<=> x = 12 (tm)
Vậy x = 12